Marginal problem with departure from characteristics for multivariate equation of Gellerstedt (Journal of Mathematics Mechanics and Computer Science, 2019)
Unambiguous solubility of the marginal problem is proved in workwith departure from characteristics for multivariate equation ofGellerstedt.